Proceedings -- The 27th International Symposium on Automation and Robotics in Construction 2010
DOI: 10.22260/isarc2010/0064
|View full text |Cite
|
Sign up to set email alerts
|

Individualization of Design Variation in Construction

Abstract: Mass Customization has been introduced and applied in a multitude of industries and should now be transferred and developed further for application in construction industry. Industrialized customization offers particular advantages compared to conventional construction as it allows addressing parameters relevant for individual and sustainable construction consequently and simultaneously. An efficient value system for industrialized customization in construction is realized through the consequent co-adaptation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In other words, the results of the content analysis indicated that the current focus of reverse logistics literature in the construction industry is primarily on end-of-life waste management. Hosseini et al [17] x Chileshe et al [18] x Hosseini et al [19] x Chileshe et al [25] x Nunes et al [26] x Arif et al [27] x Aidonis et al [30] x Aidonis et al [31] x Al-Aomar and Weriakat [32] x Arif et al [33] x Beldek et al [34] x Bock and Linner [35] x Bock and Linner, [36] x Chileshe, et al [37] x x Chinda [38] x Chinda and Ammarapala [39] x Chinda et al [40] x Dim et al [41] x Ding et al [42] x Fabbe-Costes and Jahre [43] x Fu et al [44] x Gomes et al [45] x Hosseini et al [46] x Ketikidis et al [47] x Kim et al [48] x Mathiyazhagan and Noorul [49] x x Negi et al [50] x Netro et al [51] x Ojo et al [52] x Ojo et al [53] x Qiuliang et al [54] x Rameezdeen et al [55] x Sabai [56] x Schamne et al [57] x Schultmann and Sunke [58] x Shakantu, and Emuze [59] x Shakantu et al [60] x Simon et al [61] x Sinha and Taneerananon [62] x Sobotka and Czaja [63] x Sobotka and Segan [64] x Stokić and Rado...…”
Section: Focus Of Reverse Logisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the results of the content analysis indicated that the current focus of reverse logistics literature in the construction industry is primarily on end-of-life waste management. Hosseini et al [17] x Chileshe et al [18] x Hosseini et al [19] x Chileshe et al [25] x Nunes et al [26] x Arif et al [27] x Aidonis et al [30] x Aidonis et al [31] x Al-Aomar and Weriakat [32] x Arif et al [33] x Beldek et al [34] x Bock and Linner [35] x Bock and Linner, [36] x Chileshe, et al [37] x x Chinda [38] x Chinda and Ammarapala [39] x Chinda et al [40] x Dim et al [41] x Ding et al [42] x Fabbe-Costes and Jahre [43] x Fu et al [44] x Gomes et al [45] x Hosseini et al [46] x Ketikidis et al [47] x Kim et al [48] x Mathiyazhagan and Noorul [49] x x Negi et al [50] x Netro et al [51] x Ojo et al [52] x Ojo et al [53] x Qiuliang et al [54] x Rameezdeen et al [55] x Sabai [56] x Schamne et al [57] x Schultmann and Sunke [58] x Shakantu, and Emuze [59] x Shakantu et al [60] x Simon et al [61] x Sinha and Taneerananon [62] x Sobotka and Czaja [63] x Sobotka and Segan [64] x Stokić and Rado...…”
Section: Focus Of Reverse Logisticsmentioning
confidence: 99%
“…Chileshe et al [18]; Arif et al [27]; Aidonis et al [30]; Aidonis et al [31]; Arif et al [33]; Beldek et al [34]; Bock and Linner [35]; Bock and Linner [36];…”
Section: Waste Managementmentioning
confidence: 99%
“…Management changes, including partnering agreements or integrated project delivery (IPD), would need to occur concurrently with the technological changes introduced by the modular format. As Bock and Linner 3 assert, all aspects of AEC lifecycle workflows including business strategies, modularisation, automation and customer relations have to be coordinated to deliver an integrated and customisable system. However, the focus of this article is the modular format and the refinement of concepts that will improve AEC CAD processes.…”
Section: Introductionmentioning
confidence: 99%
“…Toyota Home’s ‘Skeleton and Infill’ system is based on the combination of 10-15 steel frame units to suit the house plan form. 3 Thus, the skeleton is the structural element or chassis subsystem, while the infill comprises the sub-components. Sekisui House, currently the largest of the eight housing manufacturers in Japan 16 (p. 115), was established in 1960 from the housing division of Sekisui Chemical Co. Ltd., also the parent company of Sekisui Heim.…”
Section: Introductionmentioning
confidence: 99%